Analysis of New Workers' Compensation Claims in the Department of Defense Civilian Workforce, 2000–2012. (March 2015) - Nelson, Cameron J. L.; Bigley, Daniel P.; Mallon, Timothy M.
Abstract : Objective: This study of Department of Defense (DoD) civilian employees Workers' Compensation (WC) claims for chargeback year 2000 through 2012 aimed to analyze the frequency, rates, and costs of WC claims representing 5% of the DoD annual personnel budget. Methods: A multiyear cross-sectional study of WC claims data identified the top five most frequent causes, natures, and anatomical sites; changes in frequency, worker age, costs, and time were evaluated for trends. Results: The annual frequency and rate of new DoD WC claims decreased over time, whereas costs per new claim have increased. New claim frequencies, rates, and costs aggregated in older age groups. Conclusions: The increasing trend in costs of each claim and the overall program costs presents a need for case management. Analysis of WC claims data is necessary to help target injury prevention efforts and reduce program costs.